Has the crisis impacted the determinants of capital structure for Portuguese Public Firms? - Gonçalves, Marta Oliveira (2016)
The intention of the present dissertation is to identify the determinants of capital structure for Portuguese public firms for the period of 2005-2015 and in different sub-periods: before and during the global financial crisis, and during the European sovereign debt crisis. Thus, it proposes to empirically identify the firm characteristics and prevailing capital structure theories influencing managers’ decision-making process regarding the level of leverage. For the period 2005-2015, information regarding 57 firms from the Euronext Lisbon index was collected and analysed. Empirical results concluded that i) for the entire sample period, profitability and growth opportunities influenced negatively the level of leverage, while size and non-debt tax shields revealed to be positively related to indebtedness; ii) during the global financial crisis, profitability and liquidity were the only firm characteristics explaining the level of debt and iii) when the European sovereign debt crisis hit, growth opportunities and non-debt tax shields were the sole determinants in explaining Portuguese public firms’ leverage. The determinants influencing the proportion of long-term debt in the capital structure were also analysed for the same sample and time horizon.